Protein and Phosphate Intakes are Associated with Hyperphosphatemia in Hemodialysis Patients at Sanglah Hospital, Bali, Indonesia - Made Dyah Vismita Indramila Duarsa; Yenny Kandarini; Gede Wira Mahadita; Ni Nyoman Shinta Prasista Sari (Faculty of Medicine, Universitas Padjadjaran, 2022)
Increased chronic kidney disease (CKD) mortality rate is significantly associated with increased blood phosphate levels. Hyperphosphatemia control is one of the main focuses in the management of hemodialysis (HD) patients. A high protein diet has been suggested to prevent malnutrition in hemodialysis patients. However, a high protein and phosphorus diet has the risk of increasing the phosphate level in the blood circulation, leading to a higher mortality rate of hemodialysis patients. This study aimed to prove that the level of protein and phosphate intake is associated with hyperphosphatemia in CKD patients with routine HD. This was cross-sectional analytical study conducted from September to October 2020 on 66 CKD patients who underwent hemodialysis. Subject characteristics and phosphorus and protein intake data were obtained from a questionnaire food recall adapted from the Food and Agriculture Organization of the United Nations. Data consumption patterns were processed using the nutritional survey software to obtain the nutritional values. Data were analyzed using the Chi-Square test to identify the relationship and risk between hyperphosphatemia and diet protein, phosphorus, and protein-phosphorus ratio. The confidence level in this study was 95%. There was a significant relationship between protein and phosphorus intake in hyperphosphatemia in CKD patients. The risk factors for hyperphosphatemia were high phosphorus intake (p=0.018; OR=3.886;95% CI: 1.212–12.460) and adequate protein intake (p=0.035; OR=3.674; 95% CI: 1.049-12.865). This study showed no significant relationship between phosphorus-protein ratio, protein-phosphorus ratio, and hyperphosphatemia incidence. In conclusion, high protein intake and excessive phosphorus intake provide a significant relationship to the incidence of hyperphosphatemia in CKD patients undergoing routine hemodialysis.